2021
DOI: 10.1002/prp2.873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol and its formulation components on macrophages and neutrophils in obese and lean animals

Abstract: We hypothesized whether propofol or active propofol component (2,6‐diisopropylphenol [DIPPH] and lipid excipient [LIP‐EXC]) separately may alter inflammatory mediators expressed by macrophages and neutrophils in lean and obese rats. Male Wistar rats ( n = 10) were randomly assigned to receive a standard (lean) or obesity‐inducing diet (obese) for 12 weeks. Animals were euthanized, and alveolar macrophages and neutrophils from lean and obese animals were exposed to propofol (50 µM), activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…BALF was centrifuged (300×g, 5 min) and the cell pellet was resuspended in 2 mL od 1× PBS. Blood and BALF cells were slowly transferred to a tube containing Ficoll-Paque (Sigma, St Louis, MO, United States), then centrifuged (400×g at 20°C) for 30 min to isolate mononuclear and polymorphonuclear cells over the density gradient created by centrifugation (25)(26)(27)(28)(29). Mononuclear and polymorphonuclear cells were then treated with red blood cell lysis buffer (Sigma) for 5 min, washed twice with 1× PBS, and centrifuged (400×g at 20°C) for 5 min.…”
Section: Isolation Of Neutrophils and Macrophages From Balf And Bloodmentioning
confidence: 99%
“…BALF was centrifuged (300×g, 5 min) and the cell pellet was resuspended in 2 mL od 1× PBS. Blood and BALF cells were slowly transferred to a tube containing Ficoll-Paque (Sigma, St Louis, MO, United States), then centrifuged (400×g at 20°C) for 30 min to isolate mononuclear and polymorphonuclear cells over the density gradient created by centrifugation (25)(26)(27)(28)(29). Mononuclear and polymorphonuclear cells were then treated with red blood cell lysis buffer (Sigma) for 5 min, washed twice with 1× PBS, and centrifuged (400×g at 20°C) for 5 min.…”
Section: Isolation Of Neutrophils and Macrophages From Balf And Bloodmentioning
confidence: 99%
“…An animal model demonstrated that propofol and lipid excipients had different immunomodulatory effects in obesity, and the active components in propofol increased the expression of IL-10 and M2 phenotypes in macrophages from adipose tissue. Propofol and its active components increased IL-6 expression in obese animals ( Heil et al, 2021 ). With the increase in the obese population, understanding the immune regulation of propofol on macrophages in obese patients will be helpful for proposing an anesthesia management program.…”
Section: Propofol Regulation Of Macrophage Activation and Functionmentioning
confidence: 99%
“…Increased expression of glucose transporter 1 (GLUT1) on the surface of macrophages in adipose tissue suggests that GLUT1 is associated with inflammation in vivo . Propofol also regulated the metabolism of macrophages, which regulates the metabolism of activated macrophages by inhibiting the overexpression of ROS and decreasing the expression of GLUT1 ( Heil et al, 2021 ). Arteriosclerosis is a type of inflammatory vascular disease, and the regulation of propofol has a positive effect on arteriosclerosis formation.…”
Section: Propofol Regulation Of Macrophage Activation and Functionmentioning
confidence: 99%